Great expectations - Linson, Art 1942-; Cuaron, Alfonso 1961-; Hawke, Ethan 1970-; Paltrow, Gwyneth; Azaria, Hank 1964- (Twentieth Century Fox Home Entertainment, 1998)
The moment young Finn sets eyes on Estella, she becomes his inspiration...and his obsession. Years later, thanks to a mysterious benefactor, aspiring artist Finn is off to New York, where he is reunited with the icy and beautiful Estella. When she agrees to model for him, Finn's dearest hopes may at last be realized-along with his darkest fears!